Progress in the Design of Cooperative Heterogeneous Catalytic Materials for C–C Bond Formation. (17th June 2019) - Khoury, Christine; Gadipelly, Chandrakanth; Pappuru, Sreenath; Shpasser, Dina; Gazit, Oz M.
Abstract: The application of cooperative heterogeneous catalysts for the promotion of C–C bond formation is of great potential for making such chemical processes more sustainable. In the design of such materials, the main challenges are to form specific catalytic sites and to control the cooperative interactions. Because of the high complexity inherent to cooperative active site interactions, much of the research is focused on so called "enzyme inspired‐materials." The current Progress Report identifies three material subgroups that are characterized by a rigid‐ordered backbone (layered material), a flexible backbone (polymer based), or a constrained‐flexible‐ordered backbone (metal organic frameworks). In each of these material types, examples that illustrate how key structural and chemical characteristics functions are associated with the efficient promotion of the cooperative mechanism are highlighted. The limitations and strengths of each of the systems are considered with the aim of providing an outlook with regard to the minimum requirements needed to construct an efficient cooperative catalytic material. Given the current accumulated common knowledge in this area, it is suggested that getting inspiration from the synthetic existing systems is perhaps more beneficial than from enzymes. Abstract : Recent developments in the synthesis of cooperative catalytic materials for C–C coupling are examined with the aim of identifying the minimum material complexity required to efficiently promote such interactions. Three classes of materials are identified as the most prominent for inducing cooperative interactions. The limitations, strengths, and basic properties that distinguish each of these materials classes are critically assessed.